Behavioral alterations due to visuo-kinesthetic deprivation in rats - Espinoza C., Sergio (Revista de Psicología, 1993)
The objective of this work was to replicate in rats the visuo-kinesthetic coordination deprivation experiments previously carried out by Held & Ilein in cats. We wanted to see if it was possible to produce the same type of alterations in visually guided behavior, particularly depth perception failures. Pairs of rats were used. In each pair there was an active and a passive animal. The active received visual stimulation concurrent with the locomotion movements. The movement was mechanically transmitted to the passive. It received the same visual stimulation, but not concurrent with his own movements. Our results showed, in the passive rats, a detriment comparable to that of the passive cats. This was evidenced by a statistically significant lower performance in the depth discrimination tests. Thus, the validity of our hypothesis that the development of visually guided behavior in rats is influenced by the same type of variables as in cats was verified.